Overexpression and Inhibition of 3-Hydroxy-3-Methylglutaryl-CoA Synthase Affect Central Metabolic Pathways in Tobacco. (19th December 2020) - Liao, Pan; Lung, Shiu-Cheung; Chan, Wai Lung; Hu, Menglong; Kong, Geoffrey Kwai-Wai; Bach, Thomas J; Hao, Quan; Lo, Clive; Chye, Mee-Len
Abstract: Little has been established on the relationship between the mevalonate (MVA) pathway and other metabolic pathways except for the sterol and glucosinolate biosynthesis pathways. In the MVA pathway, 3-hydroxy-3-methylglutaryl-CoA synthase (HMGS) catalyzes the condensation of acetoacetyl-CoA and acetyl-CoA to form 3-hydroxy-3-methylglutaryl-coenzyme A. Our previous studies had shown that, while the recombinant Brassica juncea HMGS1 (BjHMGS1) mutant S359A displayed 10-fold higher enzyme activity than wild-type (wt) BjHMGS1, transgenic tobacco overexpressing S359A (OE-S359A) exhibited higher sterol content, growth rate and seed yield than OE-wtBjHMGS1. Herein, untargeted proteomics and targeted metabolomics were employed to understand the phenotypic effects of HMGS overexpression in tobacco by examining which other metabolic pathways were affected. Sequential window acquisition of all theoretical mass spectra quantitative proteomics analysis on OE-wtBjHMGS1 and OE-S359A identified the misregulation of proteins in primary metabolism and cell wall modification, while some proteins related to photosynthesis and the tricarboxylic acid cycle were upregulated in OE-S359A. Metabolomic analysis indicated corresponding changes in carbohydrate, amino acid and fatty acid contents in HMGS-OEs, and F-244, a specific inhibitor of HMGS, was applied successfully on tobacco to confirm these observations. Finally, the crystal structure of acetyl-CoA-liganded S359A revealed that improved activity of S359A likely resulted from a loss in hydrogen bonding between Ser359 and acyl-CoA, which is evident in wtBjHMGS1. This work suggests that regulation of plant growth by HMGS can influence the central metabolic pathways. Furthermore, this study demonstrates that the application of the HMGS-specific inhibitor (F-244) in tobacco represents an effective approach for studying the HMGS/MVA pathway.